College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Section P.6 - Factoring - P.6 Exercises: 29

Answer

$(x-y+3)(x+y+3)$

Work Step by Step

RECALL: $A^2-B^2=(A-B)(A+B)$ Factor the difference of two squares using the formula above with $A=x+3$ and $B=y$ to obtain: $=[(x+3)-y][(x+3)+y] \\=(x+3-y)(x+3+y) \\=(x-y+3)(x+y+3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.